A user’s guide to data from Round 3 of the Pakistan Rural Household Panel Survey (PRHPS) 2014 - International Food Policy Research Institute; Innovative Development Strategies (International Food Policy Research Institute, 2017)
The Pakistan Rural Household Panel Survey (PRHPS) 2014 is the third round of the PRHPS; Rounds 1 and 2 were conducted in 2012 and 2013 respectively. This survey aims to provide a quantitative basis to identify and address urgent economic development and policy priorities in Pakistan. Many modules and questions in Round 3 are consistent with the prior rounds. PRHPS Round 3 was able to collect complete data from 1,876 households in the rural areas of three provinces namely: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK). The sample is representative of the rural areas of Punjab and Sindh provinces and of the rural areas in 11 of the districts in KPK province. The survey collected information on many topics including sources of income, nature of employment, consumption patterns, time use, assets and savings, loans and credit, education, migration, women’s decision making, economic shocks, transfers in and out, health and nutrition, and participation in social safety nets. Four